Pengaruh Likuiditas, Ukuran Perusahaan, dan Struktur Modal Terhadap Kebijakan Dividen - Asyifa , Siti Prima Lunita (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study aims to analyze the effect of Liquidity, Firm Size and Capital Structure on Dividend Policy. The liquidity variable was measured using the loan to savings ratio, the size variable was measured using the log total asset ratio, the capital structure variable was measured using the capital adequacy ratio and the policy variable was measured using the dividend payout ratio. This study uses the causality method. The population in this study are 46 companies which are all from the banking sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period. Researchers selected samples based on certain criteria (purposive sampling) with the criteria of banking companies consistently reporting financial statements and distributing dividends in 2016-2021. This study utilizes linear multiple analysis method with secondary data type and data processing using SPSS version 26. The results of this study indicate the relationship between liquidity, firm size and capital structure simultaneously affect dividend policy. Liquidity has a significant effect on dividend policy, size has no significant effect on dividend policy and capital structure has no significant effect on dividend policy.